Open-Source Software as a Driver for Digital Content E-Commerce and DRM Interoperability - Serrão, C.; Marques, J.; Dias, J.; Delgado, J. (Proc of IPDM06 - The Europe-China Conference on Intellectual Property in Digital Media, Shangai, China, 2006)
Open-source software (OSS) is one of the hottest trends in terms of the software development in the current days. It is highly discussed if this is the best model for software creation when compared to non-open-source alternatives, and most of the times this discussion is mostly driven by passion than by facts. The main rational behind this paper is to discuss the opportunities and challenges that exist behind the usage or not of OSS in the development of DRM technology, and how it can affect the existence of different interoperable DRM technologies. The authors believe that opensource is a valuable strategy to deal with the current DRM interoperability problems. Furthermore we will establish a bridge between the open-source software developments in terms of DRM (mainly the OpenSDRM project) and how it can act as a driver for DRM interoperability.